Piano Sonata no. 8 in C minor, op. 13, published by Brandus - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (France; Paris; Brandus et Cie., 2024)
Reprint of the Piano Sonata no. 8 in C minor, op. 13, by Brandus & Cie., reprinted from the plates of M. Schlesinger.